2009
DOI: 10.1016/j.archoralbio.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Axis inhibition protein 2 (AXIN2) polymorphisms and tooth agenesis

Abstract: Tooth agenesis is a common congenital disorder that affects almost 20 percent of the world’s population. A number of different genes have been shown to be associated with cases of tooth agenesis including AXIN2, IRF6, FGFR1, MSX1, PAX9, and TGFA. Of particular interest is AXIN2, which was linked to two families segregating oligodontia and colorectal cancer. We studied two collections of families affected with tooth agenesis and tested them for association with AXIN2. Significant association between tooth agene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 18 publications
3
49
1
3
Order By: Relevance
“…Recent genetic studies have provided information about a number of genes related to tooth agenesis. Several genetic variations and mutations in AXIN2 (7), BMP4 (8), MMPs (MMP1 and MMP20) (9), PAX9 (10,11), MSX1 (10), TGFB3 (8), and WNT10A (12,13) have been associated with tooth developmental failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic studies have provided information about a number of genes related to tooth agenesis. Several genetic variations and mutations in AXIN2 (7), BMP4 (8), MMPs (MMP1 and MMP20) (9), PAX9 (10,11), MSX1 (10), TGFB3 (8), and WNT10A (12,13) have been associated with tooth developmental failure.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signaling is essential for tooth development as indicated by transgenic mouse experiments (Mikkola and Millar, 2006). Mutations and polymorphisms in AXIN2, an intracellular antagonist of Wnt signaling, have been associated with tooth agenesis (Lammi et al, 2004;Mostowska et al, 2006;Callahan et al, 2009). WNT10A mutations have also been reported in patients with tooth agenesis (Kantaputra and Sripathomsawat, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of polymorphisms and tooth agenesis are rare, with most focusing on PAX9, MSX1 and AXIN2 (Mostowska et al, 2006;Bianch et al, 2007;Callahan et al, 2009;Silva et al, 2009). Furthermore, only two studies have focused on the Chinese population (Pan et al, 2008;Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The association of the gene to tooth agenesis was first found in a Finnish family with a predisposition for colorectal cancer [24]. It has been shown that the AXIN2 mutations may also be responsible for sporadic forms of incisor agenesis [76].…”
Section: Axin2 Genementioning
confidence: 99%